Applications of ultrasonography in ruminants (III): udder andgenital system of the male - A review - LAZARIDIS (Λ.Ι. ΛΑΖΑΡΙΔΗΣ), L. J.; BROZOS (Χ.Ν. ΜΠΡΟΖΟΣ), C. N.; KIOSSIS (E.A. ΚΙΟΣΗΣ), E. A. (Journal of the Hellenic Veterinary Medical Society, 2017)
The main advantage of ultrasonography for examination of the udder, the teats and the genital system of male ruminants is the ability for real time observation of the respective anatomical region, with no need of invasive procedures and with the benefit to image superficial and deeper anatomical structures. For the examination of these two systems, one can use linear array and sector scanner probes with frequencies 3.5-12.0 MHz for udder/teats and 5.0-7.5 MHz for the genital system of male ruminants. The method and the direction of the probe differ depending on the organ being examined and the image observed can differ depending on the organ and the presence of abnormalities. Main pathological conditions that can be diagnosed ultrasonographically are in the udder mastitis, haematomas and foreign bodies and in the teats stenosis, inflammatory lesions, milkstones or foreign bodies, haematomas and abscesses. Pathological conditions in the genitalia of male ruminants, including orchitis, testicular cysts, epididymitis, abscesses, haematomas and tumours, can also be diagnosed ultrasonographically.